Mutation Detection in the Menkes Gene Using the Protein Truncation Test - Lisbeth Birk Møller; Nina Horn (SAGE Publishing, 2008)
Menkes disease (MD) is a rare recessively inherited lethal disorder of copper metabolism. The gene ATP7A defective in MD consists of 23 exons and the coding region encompasses 4500 bp. About 300 distinct mutations, representing all types, have been identified in ATP7A. However all mutations identified so far in the exon 2 to exon 7, corresponding to 1869 bp of the coding sequence, result in truncated protein products. No missense mutations have been identified in this region. As about 30% of the total number of mutations identified are located in exon 2 to exon 7, we have designed a protein truncation test (PTT) for rapid detecting of mutations in this part of the gene. In order to determine the applicability of the test, we analysed RNA obtained from eleven MD patients with known mutations in this region. As a truncated product could be identified in all the included samples, PTT proves to be a useful technique for rapid detection of mutations in the N-terminal part of the ATP7A gene. Furthermore as MD is a X-linked disease, normally only affecting boys, the risk of false negative results, due to nonsense mediated RNA decay, leading to allelic exclusion, can be left out of account.